Emotional Intelligence on Peer Conformity in Late Adolescence - Yunalia, Endang Mei; Etika, Arif Nurma (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Self-identity development in adolescents marked by the joining of youth in peer groups that can foster peer conformity. Emotional intelligence is needed by adolescents so that adolescents can avoid negative conformity. The aims of this research is analyze the correlation between emotional intelligence and peer conformity in late adolescence. This correlational analytic study was conducted on 191 respondents at “X” University who were selected using simple random sampling technique. The emotional intelligence was measured using a questionnaire that adapted Goleman's theory, while peer conformity was measured using a peer conformity questionnaire. Emotional intelligence and peer conformity data were analyzed using Spearman Rank test. Spearman Rank test showed p value 0.001 <α (0.005), r value = -0.245, so there is a correlation between emotional intelligence and peer conformity in adolescents with a negative correlation. That is, the higher level of adolescent emotional intelligence results in lower conformity with peers.